PENGABDIAN MASYARAKAT OLEH DEPARTEMEN UROLOGI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA BERUPA PENYULUHAN DAN SKRINING BATU GINJAL DAN PEMBESARAN PROSTAT DI KELURAHAN SESETAN DENPASAR - Tirtayasa, Pande Made Wisnu; Prayudi, I Nyoman Gede; Pramana, Ida Bagus Putra; Yudiana, I Wayan; Santosa, Kadek Budi; Duarsa, Gede Wirya Kusuma (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The two most common diseases in the field of urology are prostate enlargement and kidney stone disease. The main principles of health promotion and treatment are preventive and curative actions. To reduce the incidence of kidney stones and prostate enlargement, preventive measures include providing education and health screening to the community. In addition to education on kidney stones and prostate enlargement diseases, this community service activity will conduct screenings for kidney stones and prostate enlargement using ultrasound equipment. The targeted outcomes include increasing public knowledge about kidney stone disease and prostate enlargement, as well as screening for kidney stones and prostate enlargement.